Isolated cardiac valve involvement in smoldering adult T-cell leukemia/lymphoma - Aguilar, Cristian (2023)
Adult T-cell leukemia/lymphoma (ATLL) is an aggressive mature T-cell neoplasm caused by infection with the Human T-cell Lymphotropic Virus Type 1 (HTLV-1). Cardiac involvement in patients with ATLL is infrequent, and when it happens it is usually seen in aggressive ATLL subtypes. However, ATLL presenting as isolated cardiac valve involvement is extremely rare. To date, only three histologically proven cases of ATLL with isolated cardiac valve involvement have been reported. Herein, we describe a 61-year-old Peruvian man who presented heart failure symptoms secondary to progressive cardiac valve infiltration. The patient underwent mitral valve replacement with a mechanical prosthesis. Histopathological evaluation of the resected valve revealed leaflet thickening with a nodular appearance due to fibrous tissue containing atypical T-lymphocytes with Foxp3 expression, infiltrating all layers of the resected valve. Interestingly, tumor cells were distributed around an incidental venous malformation (i.e., cavernous hemangioma). Postoperative evaluation demonstrated positive serology for HTLV-1, and a diagnosis of ATLL was established. Postoperative positron emission tomography/computed tomography did not show lesions outside the heart and cell blood counts were within normal range with low level of circulating CD4+ CD25+ lymphoma cell counts (7%); therefore, patient's disease was considered as smoldering ATLL and a “watch and wait” strategy was pursued. Currently, the patient is alive with no progression of disease after 18 months from diagnosis. Isolated cardiac valve involvement by ATLL should be considered in the differential diagnosis of HTLV-1 carriers with progressive heart failure, even when systemic lymphoma involvement is absent or not apparent.